Importance of preoperative diagnosis for management of patients with suspected retroperitoneal sarcoma. Issue 4 (2nd August 2017) - Gyorki, David E.; Choong, Peter F. M.; Slavin, John; Henderson, Michael A.
Abstract : Soft tissue sarcoma is an umbrella term which encompasses over 60 histological tumour types. Approximately 15% of soft tissue sarcomas arise in the retroperitoneum. This complex group of tumours poses unique management challenges due to their often large size, histological heterogeneity and complexity of anatomical relationships. This review discusses the management of retroperitoneal tumours including the need for preoperative diagnosis, the evidence for neoadjuvant radiotherapy, the role of multivisceral resection and the importance of a multidisciplinary team approach.